Correlation between iron profile and severity of coronary artery lesion in patients with non-ST segment elevation myocardial infarction - Syarifuddin, Fairuz; Andika Sitepu; Abdullah Afif Siregar; Zulfikri Mukhtar; Cut Aryfa Andra; Teuku Bob Haykal; Harris Hasan (Universitas Brawijaya, 2025)
BACKGROUND: Excessive iron has been shown to increase the atherosclerosis process through the help of non-transferrin-bound iron (NTBI). OBJECTIVE: This study aimed to ascertain the association between iron profile and the severity of coronary artery lesions in patients with acute non-ST segment elevation myocardial infarction (NSTEMI). METHOD: This observational analytical study with a cross-sectional design was conducted from February to September 2024 at Adam Malik General Hospital. NSTEMI patients planned for coronary angiography were examined for iron profile, including serum iron, total iron binding capacity (TIBC), and transferrin saturation. Coronary artery lesion severity was evaluated using the synergy between percutaneous coronary intervention with taxus and cardiac surgery (SYNTAX) score. RESULTS: This study involved 72 subjects. The results showed there were no correlations between serum iron levels and SYNTAX scores (p = 0.891) and transferrin saturation with SYNTAX scores (p = 0.545). Nevertheless, TIBC and SYNTAX score were negatively correlated (p = 0.004) with a weak correlation coefficient (r = -0.334). CONCLUSION: TIBC levels are inversely correlated with the severity of coronary artery lesions. However, transferrin saturation and serum iron have not been shown to correlate with the severity of coronary artery lesions.